2006
DOI: 10.1007/s10725-006-9123-5
|View full text |Cite
|
Sign up to set email alerts
|

Seed enhancement with cytokinins: changes in growth and grain yield in salt stressed wheat plants

Abstract: Cytokinins are often considered abscisic acid (ABA) antagonists and auxins antagonists/synergists in various processes in plants. Seed enhancement (seed priming) with cytokinins is reported to increase plant salt tolerance. It was hypothesized that cytokinins could increase salt tolerance in wheat plants by interacting with other plant hormones, especially auxins and ABA. The present studies were therefore conducted to assess the effects of presowing seed treatment with varying concentrations (100, 150 and 200… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
63
0
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 105 publications
(75 citation statements)
references
References 30 publications
5
63
0
2
Order By: Relevance
“…Recently matured top leaves were used for the determination of different phytohormones at boot stage. Auxins (IAA, IBA) and ABA were extracted and purified as described by Kusaba et al (1998), with some modifications (Iqbal et al, 2006). The quantification of plant hormones was done by high performance liquid chromatograph (HPLC) using authentic standards run through for the whole procedure, as previously described (Iqbal et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Recently matured top leaves were used for the determination of different phytohormones at boot stage. Auxins (IAA, IBA) and ABA were extracted and purified as described by Kusaba et al (1998), with some modifications (Iqbal et al, 2006). The quantification of plant hormones was done by high performance liquid chromatograph (HPLC) using authentic standards run through for the whole procedure, as previously described (Iqbal et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Katzman et al (2001) also reported that soaking/washing in NaCl/water remove inhibitors from the pericarp and also enhance seed germination and vigor to perform well under high temperature and normal conditions. Use of growth regulators has ameliorated the drastic effect of salinity in several crops (Egamberdieva, 2009;Iqbal et al, 2006;Iqbal and Ashraf, 2010). Therefore, we tried several seed treatments to enhance germination and vigor of spinach seeds.…”
Section: Discussionmentioning
confidence: 99%
“…Significant improvement in germination of spinach due to seed treatment with bleach and hydrogen peroxide was also recorded by Katzman et al (2001), which further support our results. Germination enhancement in response to priming using distilled water (Amjad et al 2007), IAA (Afzal et al, 2005) and cytokinins (Iqbal et al, 2006) has been reported in various crops. Priming with IAA might have increased the endogenous level of GA (Wolbang et al, 2004), that is supposed to reduce the endogenous ABA (Gonai et al, 2004), and thus promoted seed germination, emergence and vigor of spinach seeds.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations